The Role Of French Documentaries In The Promoting Of the Algerian Tourist Destination - بن شرّاد محمد أمين (International Journal of Social Communication, 2022)
This article aims to identify how French tourist documentaries promote the Algerian tourist destination and its components through a case study of the French documentary film “un été en Algerie” through the researcher monitoring the most important elements of tourism in Algeria in French documentaries and the way they are presented in a the film, based on the approach of semiological analysis of the film content presented in the French documentary under study, in order to understand and dismantle the approved method of tourism marketing.